Pengukuran Waktu Kerja Karyawan Bengkel Hardchrome CV. Abad 21 Samarinda - Jonathan, Robin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
The research objective was to determine the time of labor standards hardchrome coating at the CV. Abad 21 in Samarinda. Research carried out for 2 months at the CV. Abad 21 in Samarinda with the object of research islimited regarding the calculation of working time for coating hardchrome workmanship. Data collected in the study include: an overview of hardchrome business, primary and secondaryobservational data, and the amount of labor. Data collection techniques used were: (1) observation, (2) interview, (3) documentation, and (4) the study of literature, namely the collection of data fromreports or records owned by CV. Abad 21 in Samarinda. The results indicated that: (1) the average time hardchrome coating at the CV. Abad 21 in Samarindaduring 5 times of observation is 501 minutes or 8 hours 21 minutes (2) the normal time hardchromecoating at the CV. Abad 21 in Samarinda is 501 minutes or 8 hours 21 minutes; and (3) coatinghardchrome standard time at the CV. Abad 21 in Samarinda by using the leeway factor of 15% ofnormal time is 576 hours or 9 hours 36 minutes.